Clinical Observation on Multi Spectral Irradiation for Middle and Old Aged Osteoporosis Patients with Vitamin D Deficiency - Jun XING; Zhenfang MA; Yahui WANG; Yi RU; Jianfeng LU; Li YAN; Jingke AN (康复学报)
Objective:To observe the clinical effect of multi spectral irradiation on middle and old aged osteoporosis patients with vitamin D deficiency.Methods:102 middle and old aged osteoporosis patients with vitamin D deficiency were randomly assigned to the treatment group and control group, and 51 patients were in each group. The treatment group received the irradiation of spinal column, abdomen and pain joints by using ATWL-YY-Ⅰtype production of multi band spectral instrument, and the control group received natural illumination. Two parts were irradiated per day, and the irradiation lasted for 30 days. The visual analog scale (VAS) were used to assess the extent of bone pain, bone mineral density (BMD) value and levels of vitamin D, blood calcium, blood phosphorus and alkaline phosphatase in patient's body were detected, and the changes of safety indexes such as blood glucose, total cholesterol, creatinine, glutamate pyruvate transaminase and glutamic-oxal (o) acetic transaminase were observed.Results:After 30 day's therapy, the bone pain VAS score and alkaline phosphatase level were decreased compared with those before treatment (P<0.05), and the BMD value and vitamin D level were increased compared with those before treatment (P<0.05). There was no significant difference in levels of blood glucose, total cholesterol, creatinine, glutamate pyruvate transaminase and glutamic-oxal (o) acetic transaminase of two groups before and after treatment.Conclusion:Multi spectral irradiation therapy has a good effect on middle and old aged osteoporosis patients with vitamin D deficiency.